Burden of disease attributable to risk factors in European countries - Gorasso, Vanessa (2023)
Funding Information: The authors wish to thank Maarten Engel from the Erasmus MC Library for developing and updating the search strategies. The authors would like to acknowledge the networking support from COST Action CA18218 (European Burden of Disease Network; www.burden-eu.net ), supported by COST (European Cooperation in Science and Technology; www.cost.eu ). Publisher Copyright: © 2023, The Author(s).